Cytological organization of the alpha component of the anterior olfactory nucleus and olfactory limbus - Larriva-Sahd, Jorge A. (Frontiers in Neuroanatomy, 2012)
This study describes the microscopic organization of a wedge-shaped area at the intersection of the main (MOB) and accessory olfactory bulbs (AOBs), or olfactory limbus (OL), and an additional component of the anterior olfactory nucleus or alpha AON that lies underneath of the AOB. The OL consists of a modified bulbar cortex bounded anteriorly by the MOB and posteriorly by the AOB. In Nissl-stained specimens the OL differs from the MOB by a progressive, antero-posterior decrease in thickness or absence of the external plexiform, mitral/tufted cell, and granule cell layers. On cytoarchitectual grounds the OL is divided from rostral to caudal into three distinct components: a stripe of glomerular-free cortex or preolfactory area (PA), a second or necklace glomerular area, and a wedge-shaped or interstitial area (INA) crowned by the so-called modified glomeruli that appear to belong to the anterior AOB. The strategic location and interactions with the main and AOBs, together with the previously noted functional and connectional evidence, suggest that the OL may be related to both sensory modalities. The alpha component of the anterior olfactory nucleus, a slender cellular cluster (i.e., 650 × 150 μm) paralleling the base of the AOB, contains two neuron types: a pyramidal-like neuron and an interneuron. Dendrites of pyramidal-like cells (P-L) organize into a single bundle that ascends avoiding the AOB to resolve in a trigone bounded by the edge of the OL, the AOB and the dorsal part of the anterior olfactory nucleus. Utrastructurally, the neuropil of the alpha component contains three types of synaptic terminals; one of them immunoreactive to the enzyme glutamate decarboxylase, isoform 67.